2012
DOI: 10.1051/0004-6361/201218772
|View full text |Cite
|
Sign up to set email alerts
|

[FeII] as a tracer of supernova rate in nearby starburst galaxies

Abstract: Context. Supernovae play an integral role in the feedback of processed material into the ISM of galaxies making them responsible for much of the chemical enrichment of the universe. The rate of supernovae can also reveal star formation histories. These rates are usually measured through the nonthermal radio continuum luminosity; however, a correlation between near-infrared [FeII] emission and supernova remnants has also been noted. Aims. We aim to find a quantitative relationship between the [FeII] at 1.26 μm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 71 publications
7
36
0
Order By: Relevance
“…The dustattenuated Pa-α emission map was obtained from the F190N narrow-band line+continuum image after the subtraction of the adjacent continuum emission obtained with the F187N filter. In order to correct the Pa-α map for the significant extinction (e.g., Neff et al 1990;Alonso-Herrero et al 2001;Kotilainen et al 2001;Rosenberg et al 2012), we used the EW map of the emission line plus two broadband NIR continuum images obtained at 1.6 and 2.2 um.…”
Section: Discussionmentioning
confidence: 99%
“…The dustattenuated Pa-α emission map was obtained from the F190N narrow-band line+continuum image after the subtraction of the adjacent continuum emission obtained with the F187N filter. In order to correct the Pa-α map for the significant extinction (e.g., Neff et al 1990;Alonso-Herrero et al 2001;Kotilainen et al 2001;Rosenberg et al 2012), we used the EW map of the emission line plus two broadband NIR continuum images obtained at 1.6 and 2.2 um.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the [Fe II] lines may be produced by an SNR population of ages up 10 4 years, while radio SNRs are a younger population of a few hundred years old. Rosenberg et al (2012) found a nearly linear relationship between the 1.26 µm [Fe II] luminosity and the supernova rate in a sample of 11 nearby starburst galaxy centers. This relationship is valid for normal SF galaxies but does not hold for extreme ultraluminous galaxies.…”
Section: Supernovae In Starburst Regionsmentioning
confidence: 95%
“…If the central Brγ excitation is assumed to be originating from stars only, i.e., no excitation by AGN radiation, the luminosity of Brγ in this region can be used to determine a star formation rate (SFR; Panuzzo et al 2003;Valencia-S. et al 2012). We derive an upper limit for the SFR within a 1 radius around the nucleus of 1.4 × 10 Rosenberg et al 2012;Esquej et al 2014, and references therein) compared to other non-starburst galaxies, particularly with regard to the assumption that all of the central Brγ and [Fe ] emission is attributed to star formation, which is an unlikely scenario in a Seyfert like galaxy.…”
Section: Ionized Gasmentioning
confidence: 99%